Social responsibility and women's acquisition of secondhand clothing - Charbonneau, Jill Skinner, author; Makela, Carole J., advisor; Timpson, William M., committee member; Davies, Timothy Gray, 1942-, committee member; Eckman, Molly, committee member (Colorado State University. Libraries, 2008)
The purpose of this study was to investigate women’s motivations for acquiring and wearing secondhand clothing. It specifically targets women as consumers of secondhand clothing either for themselves or their families. The goal was to discover whether women’s acquisition of secondhand clothing is linked to social responsibility. Major research questions focused on motivations and factors for acquiring and wearing secondhand clothing and what is done when clothing is no longer needed, wanted, or used. This study followed the guidelines of phenomenology to understand and scrutinize the lived experiences of women. This was achieved by asking women to describe and share motivations for acquiring and wearing secondhand clothing. Purposive and snowball sampling were used to garner a sample of 23 women for three focus groups. Experiences of acquiring or wearing secondhand clothing for themselves and their families were analyzed from a written survey and focus group transcripts to create a profile of the socially responsible clothing consumer. Recommendations for academia are to integrate socially responsible practices into apparel and textile design and merchandising classes. Other suggestions are for thrift stores to organize clothing by size and color and have clean dressing rooms and programs with curb pickup of clothing with other recyclables as newspapers, bottles, and cans.
Department Head: Timothy Gray Davies.